(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2022)
This research paper has elucidated significant factors regarding the integration of Pakistani migrants living in South Korea (S.K). Pakistan stands at the sixth spot in terms of overseas migrant workers. The migration happened due to a few reasons such as lack of access to higher education with standardized scientific equipment for experimental use, poor financial and political situation, and to gain better economic opportunities which improve their as well as families’ living standards. The open-ended interviews were conducted with the Pakistani migrants living in S.K. The subject of the study is Pakistani migrants living in Jeolla Namdo, the capital city of Gwangju, South Korea. The purpose of this study is to investigate to what extent Pakistani migrants are integrated with the host community and in which area they are facing hindrances. During interviews, the participants were asked about the basic purpose of migration to S.K, daily life, and how they celebrate their cultural and religious festivities. How do they manage their lives in the host community? According to this study, most Pakistani migrants came to Korea for education, followed by business category and joining the family. Before coming to Korea, they did not learn the Korean language, and after arrival, they realized that the language barrier and availability of halal food are real troubles. In Korea, it is difficult to get halal edible items, even though it is essential regarding Muslim religious beliefs. None of the respondents eats pork and other cooked meat available in the restaurants because the meat is not halal. There are insufficient grocery stores to purchase the affirmed halal meat. This study demonstrates that the integration of Pakistani migrants is moderate, yet a gigantic change in three things such as greetings style, sense of dressings, and food preferences is seen that is integrated from the host community. In the case of residence location preferences, the majority of Pakistani migrants do not have any hesitation to live in a non-Muslim populated area. They feel safe everywhere in Korea. Concerning the children, their integration level is high because they can easily make Korean friends. Children have adopted the language very quickly and face no barriers; they speak Korean very well too. The article’s findings offer a few suggestions to the government of South Korea that will help to improve integration and multiculturalism. It is recommended that the Korean government should amend its policy in migrants’ favor, this will positively change general people’s mindset. This will promote the concept that Korean culture is becoming multi-cultural from monoculture. The government of South Korea should consider issues creating hindrances related to integration such as the availability of migrants’ worship places, easy and everywhere availability of required edible halal food, and make easier the process of getting a permanent residence-ship. This will pull in more migrants, which will improve integration processes. Keywords: Integration, Multiculturalism, Religious festivities, Education, Equipped laboratories, Migrants.